Astrocytes in Neurodegeneration: Inspiration From Genetics - Huang, Jingxuan; Li, Chunyu; Shang, Huifang (Frontiers in Neuroscience, 2022)
Despite the discovery of numerous molecules and pathologies, the pathophysiology of various neurodegenerative diseases remains unknown. Genetics participates in the pathogenesis of neurodegeneration. Neural dysfunction, which is thought to be a cell-autonomous mechanism, is insufficient to explain the development of neurodegenerative disease, implying that other cells surrounding or related to neurons, such as glial cells, are involved in the pathogenesis. As the primary component of glial cells, astrocytes play a variety of roles in the maintenance of physiological functions in neurons and other glial cells. The pathophysiology of neurodegeneration is also influenced by reactive astrogliosis in response to central nervous system injuries. Furthermore, those risk gene variants identified in neurodegenerations involve in astrocyte activation and senescence. In this review, we summarized the relationships between gene variants and astrocytes in four neurodegenerative diseases including Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), and Parkinson’s disease (PD), and provided insights into the implications of astrocytes in the neurodegenerations.